Big Data – Concepts, Applications, Challenges and Future Scope - SINGH, YASHWANT KUMAR; RATAWA, SURYA PRAKASH (IJRDO -Journal of Computer Science Engineering, 2017)
The term, Big Data‘ has been coined to refer to the gargantuan bulk of data thatcannot be dealt with bytraditional data-handling techniques. Big Data is still a novel concept, andin the following literature we intend to elaborate it in a palpable fashion. It commences with theconcept of the subject in itself along with its properties and the two general approaches ofdealing with it. The comprehensive study further goes on to elucidate the applications of BigData in all diverse aspects of economy and being. The utilization of Big Data Analytics afterintegrating it with digital capabilities to secure business growth and its visualization to make itcomprehensible to the technically apprenticed business analyzers has been discussed in depth.Aside this, the incorporation of Big Data in order to improve population health, for thebetterment of finance, telecom industry, food industry and for fraud detection and sentimentanalysis have been delineated. The challenges that are hindering the growth of Big DataAnalytics are accounted for in depth in the paper. This topic has been segregated into two arenasonebeing the practical challenges faces whilst the other being the theoretical challenges. Thehurdles of securing the data and democratizing it have been elaborated amongst several otherssuch as inability in finding sound data professionals in required amounts and software thatpossess ability to process data at a high velocity. Through the article, the authors intend todecipher the notions in an intelligible manner embodying in text several use-c